2013
DOI: 10.1089/jir.2012.0103
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Supplementation Improves Macrophage Functions in HIV

Abstract: In this study, we determined the effects of glutathione (GSH)-enhancing agents in restoring the levels of GSH in isolated macrophages from individuals with HIV infection thereby resulting in improved control of Mycobacterium tuberculosis. Our results indicate that treatment with N-acetyl cysteine or a liposomal formulation of glutathione (lGSH) resulted in replenishment of reduced also known as free GSH (rGSH), and correlated with a decrease in the intracellular growth of M. tuberculosis. Finally, we observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 23 publications
0
62
0
Order By: Relevance
“…A growing body of evidence suggests that NAC can affect bacterial viability inside of eukaryotic host cells [45]. To test this concept with mycobacteria we infected THP-1 cells (to reduce variability between blood donors) with M. tuberculosis , M. avium or M. bovis BCG bacilli (MOI of 10) for 3 h, replaced the media, and added NAC (10 mM) to half of the cultures.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence suggests that NAC can affect bacterial viability inside of eukaryotic host cells [45]. To test this concept with mycobacteria we infected THP-1 cells (to reduce variability between blood donors) with M. tuberculosis , M. avium or M. bovis BCG bacilli (MOI of 10) for 3 h, replaced the media, and added NAC (10 mM) to half of the cultures.…”
Section: Resultsmentioning
confidence: 99%
“…It is now known that a number of interactions may occur that prevent the de novo formation of GSH. For example, it has been shown that glutathione is decreased due to an inability to produce glutathione in the extracellular lung fluid of children with chronic asthma [45] and in the macrophages of adults with human immunodeficiency virus (HIV) [46]. …”
Section: Glutathione Sources In the Bodymentioning
confidence: 99%
“…This study demonstrates that without function of the genes needed to produce glutathione supplying the building block of glutathione production, NAC is much less efficient than supplying the whole molecule of glutathione using a liposomal encapsulation of glutathione [46]. …”
Section: Glutathione Sources In the Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was shown that this reduction correlated with the decreased levels of intracellular GSH. Furthermore, the same group had shown that the GSH levels in plasma and peripheral blood mononuclear cells of HIV-positive individuals were also compromised [40,41].…”
Section: Gsh Deficiency In Hiv Patientsmentioning
confidence: 99%